2021
DOI: 10.3390/pathogens10050616
|View full text |Cite
|
Sign up to set email alerts
|

An Outer Membrane Vesicle-Adjuvanted Oral Vaccine Protects Against Lethal, Oral Salmonella Infection

Abstract: Non-typhoidal salmonellosis, caused by Salmonella enterica serovar Typhimurium is a common fecal-oral disease characterized by mild gastrointestinal distress resulting in diarrhea, chills, fever, abdominal cramps, head and body aches, nausea, and vomiting. Increasing incidences of antibiotic resistant invasive non-typhoidal Salmonella infections makes this a global threat requiring novel treatment strategies including next-generation vaccines. The goal of the current study was to formulate a novel vaccine plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…OMVs are being explored in a variety of contexts as nanoparticle vaccines, including in the FDA-approved vaccine for meningococcal group B disease, Bexsero [ 90 ]. Other work has shown that the same OMVs can be both a vaccine and an adjuvant, thus potentially behaving as a self-adjuvanting antigen delivery system [ 89 , 91 93 ]. OMVs from the closely related F. novicida may be one novel vaccine approach for combatting tularemia.…”
Section: Current Approaches To Francisella Vaccina...mentioning
confidence: 99%
“…OMVs are being explored in a variety of contexts as nanoparticle vaccines, including in the FDA-approved vaccine for meningococcal group B disease, Bexsero [ 90 ]. Other work has shown that the same OMVs can be both a vaccine and an adjuvant, thus potentially behaving as a self-adjuvanting antigen delivery system [ 89 , 91 93 ]. OMVs from the closely related F. novicida may be one novel vaccine approach for combatting tularemia.…”
Section: Current Approaches To Francisella Vaccina...mentioning
confidence: 99%
“…By fusing S. Typhimurium EVs with S. flexneri polysaccharide determinants, protection of mice against a challenge with virulent bacteria was obtained [ 189 ]. Other authors have proposed using EVs from Burkholderia pseudomallei as an adjuvant for a heat-killed S. Typhimurium-based vaccine, and this formulation protected mice against a lethal dose of the bacterium [ 190 ].…”
Section: Therapeutic Proposals Based On Extracellular Vesiclesmentioning
confidence: 99%
“…Their strategy involved mutational inactivation of the MsbB (LpxM) lipid A acyltransferase to generate OMVs of reduced endotoxicity from Escherichia coli (E. coli) O157:H7. The results suggest that by using genetic engineeringbased approaches, the native OMVs could be modified to have both intrinsically low endotoxicity and a foreign epitope tag to establish a platform technology for developing multifunctional vaccine delivery vehicles [48][49][50][51].…”
Section: Updates On the Pre-clinical And Clinical Study On Omv-based Vaccine Developmentmentioning
confidence: 99%